2009
DOI: 10.1080/02699930801940461
|View full text |Cite
|
Sign up to set email alerts
|

Interpretive bias in social phobia: An ERP study with morphed emotional schematic faces

Abstract: Individuals with social phobia fear negative evaluation, which is most directly signalled by an angry expression of the interlocutor's face. This study investigated the processing of 3 series of schematic emotional faces, which were morphed in 7 steps from a neutral face to an angry, happy, or sad face by systematically varying features of the mouth, eyes, and eyebrows. Individuals with social phobia or spider phobia rated angry faces as more arousing than controls. Social phobics did not identify angry faces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
66
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 72 publications
16
66
5
Order By: Relevance
“…In addition, Rossignol et al (2007) reported facilitated detection of subtle changes in anger expression during face repetition in participants with non-clinical social anxiety compared to low socially anxious participants, as reflected by a reduced N2b wave around 300 ms post-stimulus. Only a few previous ERP studies investigated angry face processing in participants with clinically diagnosed SAD (Kolassa and Miltner, 2006;Kolassa et al, 2007Kolassa et al, , 2009. In contrast to the present study, these found no evidence for increased early processing of task-irrelevant angry faces, although enhanced right temporo-parietal N170 amplitudes were found during explicit emotion identification of angry faces in one study (Kolassa and Miltner, 2006).…”
Section: Early Processing Advantage For Angry Faces In Sadcontrasting
confidence: 99%
See 4 more Smart Citations
“…In addition, Rossignol et al (2007) reported facilitated detection of subtle changes in anger expression during face repetition in participants with non-clinical social anxiety compared to low socially anxious participants, as reflected by a reduced N2b wave around 300 ms post-stimulus. Only a few previous ERP studies investigated angry face processing in participants with clinically diagnosed SAD (Kolassa and Miltner, 2006;Kolassa et al, 2007Kolassa et al, , 2009. In contrast to the present study, these found no evidence for increased early processing of task-irrelevant angry faces, although enhanced right temporo-parietal N170 amplitudes were found during explicit emotion identification of angry faces in one study (Kolassa and Miltner, 2006).…”
Section: Early Processing Advantage For Angry Faces In Sadcontrasting
confidence: 99%
“…In contrast to the present study, these found no evidence for increased early processing of task-irrelevant angry faces, although enhanced right temporo-parietal N170 amplitudes were found during explicit emotion identification of angry faces in one study (Kolassa and Miltner, 2006). The lack of a processing bias for implicit social threat in these studies may be partly due to the use of schematic face stimuli (Kolassa et al, 2007(Kolassa et al, , 2009) which show a different electrophysiological response pattern than photographic faces (Kolassa et al, 2007) and may be less sensitive for detecting Figure 2 Correlation between social anxiety (SPAI total score) and cortisol-induced change in P2 amplitude for angry faces in the masked emotional Stroop task (i.e., P2 masked angry placebo À cortisol). Positive values on the x-axis indicate larger P2 amplitudes on midline electrodes (Fz, Cz, Pz) in the placebo condition, compared to the cortisol condition.…”
Section: Early Processing Advantage For Angry Faces In Sadcontrasting
confidence: 99%
See 3 more Smart Citations